A Crook is a Crook … But is He Still a Crook Abroad? On the Effect of Immigration on Destination‐Country Corruption. Issue 4 (15th December 2014) - Dimant, Eugen; Krieger, Tim; Redlin, Margarete
Abstract This paper analyzes the impact of migration on destination‐country corruption levels. Capitalizing on a comprehensive dataset consisting of annual immigration stocks of OECD countries from 207 countries of origin for the period 1984–2008, we explore different channels through which corruption might migrate. We employ different estimation methods using fixed effects and Tobit regressions in order to validate our findings. Moreover, we also address the issue of endogeneity by using the Difference‐Generalized Method of Moments estimator. Independent of the econometric methodology, we consistently find that while general migration has an insignificant effect on the destination country's corruption level, immigration from corruption‐ridden origin countries boosts corruption in the destination country. Our findings provide a more profound understanding of the socioeconomic implications associated with migration flows.